Ottoman-French-Armenian Relations Around A French Steamship Navigation Company - Süleyman; UYGUN (Gazi Akademik Bakış)
The most important instruments of expansionist policies of European states after the Industrial Revolution’s were steamship navigation companies. France’s economic, political, social and cultural areas of politics, like other European states, had serious effecs on the steamship navigation companies. Ottoman lands were very important geographic areas for France and Messageries Maritimes which is a France steam navigation company. Therefore all kinds of intruments which may serve this purpose had been used by them. In this study, we tried to reveal the effects of France’s influence policies about Ottoman Armenians which effected Messageries Maritimes Company (1851- 1914) and the direct and indirect role of the company on the Armenian cases.